Decision making in civil disputes: The effects of legal role, frame, and perceived chance of winning - Victoria Gilliland; John C. Dunn (Judgment and Decision Making, 2008)
The present study investigates the effect of framing and legal role on the propensity to accept a settlement offer by litigants in a simulated legal dispute. Participants were given four different scenarios that factorially combined legal role (plaintiff vs. defendant) and frame (positive vs. negative). The results indicated that positively framed litigants were more willing to settle than negatively framed litigants independently of legal role. These results were replicated in a second experiment that also asked participants to state their subjective probability of winning. This revealed that the propensity to settle was a joint function of frame and the perceived chance of winning. In contrast to previous research, no systematic effect of legal role was found. It is concluded that the rate of negotiated settlements of legal disputes may be increased by manipulating both of these factors.